Experiências de famílias na imunização de crianças Brasileiras menores de dois anos - Figueiredo, Glória Lúcia Alves; Pina, Juliana Coelho; Tonete, Vera Lúcia Pamplona [UNESP]; de Lima, Regina Aparecida Garcia; de Mello, Débora Falleiros (FapUNIFESP (SciELO), 2011)
This study aimed to describe the experience of families in the immunization of children under two years. Descriptive study with qualitative data analysis. Twenty-two subjects participated in unstructured interviews. Results were grouped into three categories: Practical knowledge on children's immunization; Responsibility and compulsory immunization of children; Increasing the scope of children's immunization practices. The findings highlight factors that increase vaccination rates: experience and personal fulfillment in maternity, fear of getting ill, recognizing it as good care, access, schedule flexibility, dissemination, immunization record card, immunization campaigns and availability of vaccines, and factors that increase non-vaccination rates: parent's inexperience, refusal to apply simultaneous immunization, fragmented care, absence of dialog, discrimination, false counter-indications and compulsoriness. Immunization centered on compliance with the calendar or in authoritarian situations is not tied to family care. The bond between health care professionals and families needs to be strengthened to increase the participation in child health protection and promotion measures.
Experiences of families in the immunization of Brazilian children under two years old
Keywords: Child health (public health); Immunization; Primary health care